Research on early runway incursion warning based on Petri net. (May 2023) - Tang, Xinmin; Ji, Xiaoqi
In this study, an early runway incursion warning method was developed based on a Petri net model in order to achieve zero missing and false runway incursion warnings. The runway incursion warning scenario is analyzed based on the output states of the aircraft/vehicles in the airport surface. The runway operation model based on a Petri net model was established by considering Guangzhou Baiyun International Airport as an example. In addition to the runway warning rules, the standard runway operation constraints are imposed on the Petri net model to provide early warnings in nine runway incursion scenarios. The zero missing and false early runway incursion warning method based on a Petri net model was tested based on scenario simulations and realized warning display on surveillance map.